Attitudes and knowledge of preschool children’s parents about preventive vaccinations - Orzeł-Nowak, Anita; Bińkiewicz-Śmiałek, Bińkiewicz-Śmiałek; Ścisło, Ścisło; Walewska, Elżbieta (Nursing in the 21st Century, 2015)
ATTITUDES AND KNOWLEDGE OF PRESCHOOL CHILDREN’S PARENTS ABOUT PREVENTIVE VACCINATIONSIntroduction. Despite being mandatory, the preventive vaccinations in Poland stir up numerous controversies and cause concern among parents, mostly because of potential medical complications after vaccinations. Because of the favourable epidemiological situation more and more parents are not confident whether preventive vaccinations for children are still necessary. On the other hand, scientists are warning against the recurrence of infectious diseases that have been controlled through vaccination. The ongoing discussion whether to vaccinate or not, leaves parents in dismay. On the one hand, this situation makes some parents give up vaccinating their children, on the other, promotes education and conscious decision-making processes.Aim. The aim of this study was to describe the level of the knowledge, experience and the opinion of parents of children of preschool age in the area of protective vaccination. The results can be used as educational material. Material and Methodology. The study included 102 parents of preschool children. Diagnostic survey method was applied in the research, using the author’s questionnaire.Results. Less than half of respondents (48%) knows the optimal age at which a person should be vaccinated against tuberculosis, more than half (56.9%) knows when to provide the first dose of the Polio vaccine. Approximately half of the respondents (51%) knows the diseases (measles, mumps and rubella) against which the MMR vaccine protects. The respondents know additional immunization program (82.4%). They also know such terms as the combined vaccine (90.2%) and postvaccination reaction (69.8%). The fear of vaccination was reported by approximately 5% of respondents (definitely yes). Some parents (31.7%) do not notice any concern against vaccinations, the remaining ones are worried about possible complications (30.7%), an allergic reaction and the fear of a needle prick. Parents with university education report more doubts and fears. According to 36.6% of respondents, parents should take the decision on their child vaccination, but only 6.9% have sufficient knowledge on this topic. The surveyed people who are definitely against punishment of parents who do not vaccinate children account for 19.6%. Among all of the surveyed, only one person admitted that his/her child was not vaccinated and this was his/her personal choice. The respondents benefit from recommended vaccinations (49%), mostly against rotavirus. Most of the surveyed people (69%) would vaccinate their children with recommended vaccines if they were free of charge.Conclusion. Analysis of the studies shows that parents of preschool children have an average level of knowledge about immunizations. Most respondents think that the number and the kind of mandatory vaccinations are correct. More than half of respondents believes that vaccinations of children do not endanger their lives and health. The vast majority of parents do not observe in their children the side effects after vaccination.